2017
DOI: 10.1186/s13613-017-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Venovenous extracorporeal membrane oxygenation devices-related colonisations and infections

Abstract: Background Nosocomial infections occurring during extracorporeal membrane oxygenation (ECMO) support have already been reported, but few studied infections directly related to ECMO devices. This study aims to evaluate the rate of both colonisations and infections related to ECMO devices at the time of ECMO removal.ResultsWe included all consecutive adult patients treated with venovenous ECMO (VV-ECMO) for at least 48 h during a 34-month study. At the time of ECMO removal, blood cultures, swab cultures on inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 28 publications
5
60
0
Order By: Relevance
“…The reported incidence rates of BSI occurring in patients requiring ECMO support for circulatory failure or mixed population range widely, from 3.4% to 21.1%, 1,4,[9][10][11][12][13][14][15][16] Although the incidence of BSI in our study was similar to that reported previously, a recent study that included 100 adult patients treated with venovenous ECMO and who underwent routine blood cultures showed an incidence rate of 35%, 5 which is relatively high compared to our study but might be associated with routine surveillance blood culture. Inconsistent with previous reports, 1,5,6,9-11 a prolonged duration of ECMO support was not associated with BSI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence rates of BSI occurring in patients requiring ECMO support for circulatory failure or mixed population range widely, from 3.4% to 21.1%, 1,4,[9][10][11][12][13][14][15][16] Although the incidence of BSI in our study was similar to that reported previously, a recent study that included 100 adult patients treated with venovenous ECMO and who underwent routine blood cultures showed an incidence rate of 35%, 5 which is relatively high compared to our study but might be associated with routine surveillance blood culture. Inconsistent with previous reports, 1,5,6,9-11 a prolonged duration of ECMO support was not associated with BSI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for infectious complications in adult patients receiving ECLS include older age, higher severity of illness, cannulation techniques, and duration of ECLS . Other factors such as bacterial colonization of the ECLS cannulae or membrane oxygenator were also proposed as factors contributing to increases in infectious complications in patients receiving ECLS …”
Section: Specific Ecls Management Considerationsmentioning
confidence: 99%
“…41 Other factors such as bacterial colonization of the ECLS cannulae or membrane oxygenator were also proposed as factors contributing to increases in infectious complications in patients receiving ECLS. 41,42 One of the largest cohort studies to date, which included 2298 adult patients receiving ECLS, reported a 21% prevalence of infectious complications, with 30.6 infectious episodes per 1000 ECLS days. 43 Additionally, a higher rate of infections complications was observed in adult patients requiring ECLS support for more than 14 days compared with 7 days or less (52% vs 13%, respectively; p < 0.001).…”
Section: Prophylaxis and Management Of Infectious Complicationsmentioning
confidence: 99%
“…Depending on the patient's condition, ECMO treatment may last several days or longer, but its presence is a major risk factor for blood stream infection (BSI). In previous studies, it was found that 19-32% of inserted ECMO catheters were colonized with potentially pathogenic bacteria at the point of removal and that about 10% were associated with ECMO device infection [1,2]. While BSI occurrence during ECMO is a serious complication associated with significant morbidity and mortality, its prevalence has been reported to be as much as 3-18% in adults [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely to only increase the risk of resistant strain development and can potentially lead to yeast overgrowth [4]. Given that the predominant organisms colonizing ECMO catheters were found to be gram-positive cocci and Candida species [1,2], it seems likely that skin bacteria traverse the insertion site onto the catheter, where they colonize the circuit and act as a focus for BSI. Furthermore, manipulation of hub for the use of renal replacement therapy (RRT) during ECMO, or for oxygenator function test, and exchange of oxygenator or catheters potentially pose a risk of BSI.…”
Section: Introductionmentioning
confidence: 99%